Exploring the link between public health compliance and voting patterns in the 2020 U.S. presidential election - Nkouaga, Florent (Frontiers in Political Science, 2024)
This research examines whether people's health attitudes and behaviors were linked to how they voted in the 2020 U.S. presidential election. It analyzed voters' actions using information from the 2021 African American COVID-19 Vaccine Poll (AACVP) and the 2020 Collaborative Multi-Racial Post-Election Survey (CMPS). The AACVP gives information on how well people followed public health rules, and the CMPS survey gives a wide-angle look at how people voted, including whether they were registered to vote. The research found a noticeable connection between how closely people followed health guidelines and who they voted for. People who followed the health guidelines more closely tended to vote for Biden, while those who did not follow them as much tended to vote for Trump. This pattern was also seen with mask-wearing, which was used as a sign of how well people followed health guidelines. The findings suggest that people's health views were closely connected to their political choices, showing how the pandemic turned into a political issue and how it was part of more significant issues dividing society. This study helps better understand how people's health actions are linked to their political choices during times of health emergencies.